Functional and Pragmatic Aspect of Lexical and Semantic Means of Representation of Spanish Fashion Brands - Асаєвич, Ірина Дмитрівна (Київський національний університет імені Тараса Шевченка, 2025)
The article investigates the functions of lexical and semantic means in the representation of Spanish fashion brands in the publicistic discourse of Spain. It analyses the functions of terminology in the linguistic context with positive connotations, as well as the influence of stylistic means on the formation of the brands' image and attraction of the target audience. With the help of functional-pragmatic analysis, the study examines the peculiarities of the functioning of lexical and semantic fields, metaphors and epithets that modify the perception of the brand by the mass audience. The pragmatic functions of such linguistic units include the creation of brand associations with luxury, style, modernity and accessibility. It has been found that the use of elements of popular culture, in particular references to famous personalities and mass culture, contributes to the identification of brands with a trend.

У статті досліджено функції лексико-семантичних засобів у репрезентації іспанських модних брендів у публіцистичному дискурсі Іспанії. Аналізуються функції термінології в лінгвістичному контексті з позитивною коннотацією, а також вплив стилістичних засобів на формування іміджу брендів і залучення цільової аудиторії. За допомогою функціонально-прагматичного аналізу у дослідженні проаналізовано особливості функціонування лексико-семнатичних полів, метафор та епітетів, які модифікують сприйняття бренду масової аудиторією. Прагматичними функціями таких мовних одиниць є створення асоціацій брендів із розкішшю, стилем, сучасністю та доступністю. Встановлено, що використання елементів популярної культури, зокрема згадок про відомих особистостей та посилань на масову культуру сприяє ідентифікації брендів із трендовістю.
Функціонально-прагматичний аспект лексико-семантичних засобів репрезентації іспанських модних брендів
Keywords: lexical and semantic means; publicistic discourse; Spanish fashion brands; stylistic means; functional and pragmatic analysis; лексико-семантичні засоби; публіцистичний дискурс; іспанські модні бренди; стилістичні засоби; функціонально-прагматичний аналіз